Pencegahan Korupsi Melalui Optimalisasi Tata Kelola Rehabilitasi dan Pembangunan Ruang Kelas di Indonesia - Zakariya, Rizki (Integritas : Jurnal Antikorupsi, 2020)
People have the right to education. States are obliged to provide education for citizens. Therefore, the Government of Indonesia annually allocates an education fund of at least 20% of the total National Budget. One of the allocations for the Education fund is for rehabilitation and construction of new classrooms for schools. However, even though it has been budgeted in large numbers each year, the number of lightly / severely damaged classrooms in Indonesia is still relatively high every year. This is due to governance problems in the rehabilitation and construction of classrooms, which are prone to corrupt practices. Thus, affecting the quality of buildings produced. In addition, education is a sector that has always been included in the top 5 corruption cases in Indonesia since 2015. Based on this, it is necessary to prevent and take action against corrupt practices in the education sector. Corruption Eradication Commission (KPK) is an institution that can carry out prevention and enforcement efforts with its authority. Therefore, by improving the governance of rehabilitation and classroom development in Indonesia, it will have an impact on the effective and efficient development of education in Indonesia.